Local electric field factors by a combined charge-transfer and point–dipole interaction model1. Issue 40 (7th May 2015) - Davari, Nazanin; Haghdani, Shokouh; Åstrand, Per-Olof; Schatz, George C.
<x xml:space="preserve">Abstract</x> A model for the local electric field as a linear response to a frequency-dependent external electric field is presented based on a combined charge-transfer and point–dipole interaction force-field model.